1993
DOI: 10.1016/0165-232x(93)90010-6
|View full text |Cite
|
Sign up to set email alerts
|

A simplified numerical solution of the Miller model of secondary frost heave

Abstract: We describe the method used by Fowler and Krantz ( 1993 ) which reduces the Miller model of frost heave to two linear ordinary differential equations. Numerical solutions are presented and qualitative comparison is made with a numerical solution to the full system of equations given by O'Neill and Miller ( 1985 ).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 6 publications
1
16
0
Order By: Relevance
“…Moreover, he demonstrated that a permeation boundary layer existed below the lowest ice lens across which the entire pressure drop in the water phase essentially occurs. Fowler and Noon [1993] have shown that the solution to this simplified model, which can be solved analytically, gives results in excellent agreement with a numerical solution to the full Miller model. Krantz and Adams [1996] proved that this simplified model agrees well with one‐dimensional frost heave measurements in laboratory core experiments.…”
Section: Methodsmentioning
confidence: 55%
“…Moreover, he demonstrated that a permeation boundary layer existed below the lowest ice lens across which the entire pressure drop in the water phase essentially occurs. Fowler and Noon [1993] have shown that the solution to this simplified model, which can be solved analytically, gives results in excellent agreement with a numerical solution to the full Miller model. Krantz and Adams [1996] proved that this simplified model agrees well with one‐dimensional frost heave measurements in laboratory core experiments.…”
Section: Methodsmentioning
confidence: 55%
“…Except under asymptotic conditions, these models must be solved numerically. One-dimensional, numerical solutions to the model by Miller (1977Miller ( ,1978 have been presented by O' Neill andMiller (1982, 1985), Black and Miller (1985), Fowler and Noon (1993), Black (1995) and Krantz and Adams (1996). In several instances, numerical results agree favorably with laboratory results such as those of Konrad (1989).…”
Section: Prior Studiesmentioning
confidence: 72%
“…When appropriately tuned for particular soil types, such models can reproduce the major features observed during heave. The predictive capabilities of this approach have been greatly extended by the development of asymptotic methods to aid in the solution of the model equations ͑Fowler, 1989; Fowler and Noon, 1993;Fowler and Krantz, 1994͒. It is only recently, however, that a more fundamental understanding of the factors that determine how the overburden is supported has emerged.…”
Section: Frost Heavementioning
confidence: 99%